P0849LOWER TRANSFERRIN SATURATION INDEX (TSAT) IS ASSOCIATED WITH WORSE HEALTH-RELATED QUALITY OF LIFE (HRQOL) IN NON-DIALYSIS DEPENDENT CHRONIC KIDNEY DISEASE (NDD-CKD) PATIENTS AT BOTH HIGHER AND LOWER HEMOGLOBIN LEVELS. (6th June 2020) - Guedes, Murilo; Muenz, Daniel; Zee, Jarcy; Lopes, Marcelo; Waechter, Sandra; Stengel, Benedicte; Massy, Ziad; Speyer, Elodie; Finkelstein, Fredric; Sesso, Ricardo; Pisoni, Ronald; Robinson, Bruce; et al.
Abstract: Background and Aims: Iron Deficiency (ID) is a common condition in NDD-CKD patients that is associated with poorer clinical outcomes. In different populations, such as congestive heart failure patients, treatment of ID leads to better clinical outcomes and HRQOL. However, the impact of ID on HRQOL is previously unknown among NDD-CKD individuals. We analyzed real world data from a multinational cohort of NDD-CKD stage 3 to 5 patients under nephrology care to evaluate the association between TSAT and HRQOL measures from the KDQOL-36. Method: Patients from Brazil (N=205), France (N=2015), and the US (N=293) enrolled in the Chronic Kidney Disease Outcomes and Practice Patterns Study (CKDopps, 2013 to 2019) with available TSAT, ferritin, and HRQOL data were included in the analysis. We grouped patients according to their TSAT levels as ≤15%, >15-20%, >20-30% (reference group), >30-50%, and >50%. We considered the TSAT value that preceded the HRQOL measurement closest in time as the predictor. Linear mixed regression was used to estimate the mean differences (95% CI) in physical composite summary (PCS), mental composite summary (MCS), and KDQOL-36 subdomains across TSAT categories. Models were adjusted for potential confounders. Results: 2513 patients (62% male, 44% with diabetes, mean (SD) age 67 (13) years; 48%, 44% and 8% having stage 3, 4 and 5 NDD-CKD, respectively) were included in the analysis. Mean TSAT was 25 % (10). Distribution across TSAT categories was 14%, 19%, 42%, 23, and 2%, respectively. The median [IQR] number of days between TSAT measurement and PRO collection was 24 [13, 49] days. Mean PCS was 41 (10) and MCS was 45 (11). In the multivariate analysis, TSAT ≤15% was associated with lower HRQOL scores, in particular PCS, and with less favorable effects and symptoms of kidney disease (Figure). Similarly, less favorable HRQOL scores captured in the SF-12 subdomains indicative of physical HRQOL were observed in patients with lower TSAT. The adjustment for Hb only slightly attenuated the effects, and the results were not different for subgroup of patients with hemoglobin <11.5 vs ≥ 11.5 g/dL. Conclusion: Lower TSAT levels, indicative of iron deficiency, are associated with poorer HRQOL in NDD-CKD patients, particularly for physical domains and effects of kidney disease, even after adjustment for potential confounders and stratification for normal and low hemoglobin levels. Randomized controlled trials of iron replacement therapy aiming to evaluate its impact on HRQOL among NDD-CKD individuals are needed to confirm and integrate these findings into clinical practice.